Analisis Kepedulian Siswa SMA terhadap Lingkungan Sungai di Kawasan Cimanggung dan Sekitarnya - Rina Karwatisari; Hertien Koosbandiah Surtikanti (Universitas Sebelas Maret, 2025)
Environmental issues in the river area have received less attention, even though the river plays a big role in people's lives, especially those around it. It is important to know the concern of high school students for the environment because they are the next generation of the region's future development. One of the rivers in the Cimanggung area is the Cimande River. This study aims to analyze the environmental concerns of high school students regarding the river environment in the Cimanggung Area and its surroundings. The research method used was a descriptive qualitative method, with respondents of high school students in the Cimanggung area totaling 139 respondents with an age range of 15-18 years. Data collection techniques by observation, interviews, and literature studies. The instrument used to determine the level of student concern for the environment uses a Likert scale consisting of 25 questions and 5 interview questions. The results showed that the level of student concern was broadly in the good category with an average score of 76.9. The results of observations and interviews show that the waste cont